Factors affecting the adoption of interactive digital learning tools among accounting students at Politeknik Mukah : Using UTAUT model - Ahmad, Nurul Fatihah; Mohamad, Amri; Salem, Natasha Afina (Jurnal Penyelidikan Sains Sosial, 2025)
This study investigates the factors influencing the adoption of Interactive Digital Learning Tools among accounting students at Politeknik Mukah, utilizing the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The research seeks to understand the key factors including performance expectancy, effort expectancy, social influence, and facilitating conditions, in order to uncover how these factors impact students' acceptance on interactive digital tools. The findings intended to provide information for educators and institutions in promoting effective digital engagement, which would improve student learning experiences in Malaysia’s polytechnic education system. This study used quantitative approach, with questionnaires distributed via google form and the survey link shared through WhatsApp. A total of 150 students participated in the survey. By analysing the challenges faced by accounting students, particularly in subjects that combine theory with practical application, the study contributes to our understanding of how interactive tools can improve engagement and retention. This study highlights the role of digital tools in creating flexible learning environments. Multiple regression analysis confirms that performance expectancy significantly influences adoption among accounting students, while effort expectancy, social influence, and facilitating conditions do not. The results indicate that students are more likely to adopt digital tools when they perceive clear academic benefits, such as improved understanding and efficiency in completing assignments. This finding reinforces the importance of designing digital learning environments that align with students’ expectations of performance improvement. Additionally, the study extends the UTAUT model’s theoretical application in technical education and provides practical insights for educators and institutions to develop more effective digital learning strategies.